Hot corrosion Type I of novel Co-based γ/γ′ superalloys with and without Al- and Cr-diffusion coatings - König, Till; Hagen, Sebastian; Virtanen, Sannakaisa; Galetz, Mathias C. (Materials and Corrosion - Werkstoffe und Korrosion, 2024)
Co-based γ/γ′ superalloys are in development as candidates to replace Ni-based superalloys in turbine engines, where they will be exposed to hot corrosion. The present study investigates the resistance to high temperature Type I hot corrosion of four alloys of the Co–Ni–Al–W system, which differed in their Co to Ni ratio and their W content. In addition, the alloys are tested not only uncoated but also with an Al and a Cr diffusion coating. The exposures were performed at 950°C with a Na2SO4 deposit of 2.5 mg/cm2 in air containing 0.1% SO2 for 100 and 300 h. The degradation was investigated by material loss measurements. Both coatings proved mostly protective for 100 h, while the uncoated samples were severely degraded. After the longer exposure time, only the Cr-coating remained partially protective and outmatched the Al-coating. Further, a positive influence was attributed to a higher Co to Ni ratio (1.4 vs. 0.7) and a higher W content (5 vs. 3 at%).
CRIS-Team Scopus Importer:2024-06-28
Keywords: Co-based superalloys; high temperature corrosion; hot corrosion; oxidation